Nature and extent of disciplinary practices used by school teachers - Bains, Harmesh Singh; Sareen, Manu Sharma (International Journal of Contemporary Pediatrics, 2018)
Background: The aim of the study is to analyze the nature, extent and associated factors of disciplinary practices used by school teachers. Methods: A cross-sectional analytic study. Subjects: 165 school teachers. Methods: Teachers completed a structured questionnaire, which included nature and extent of disciplinary methods used and their views on the issue. Statistical analysis was done through Chi square test. Results: 70.9% Teachers felt that physical punishment is needed to discipline school children. 58.2% of teachers indulged in the same though of these 84.2% opinioned that it may be harmful. Methods used were: counselling followed by physical punishment 41.67 % , slapping (14.6%), angry shouting (11.5), shaking (9.4), swearing (6.2), and skin pinch (3.1). Common reasons for punishment included: telling a lie (31.3%), not good at studies (28.1%),disobeying (14.6%),tantrums (7.3%) and stealing (3.1%). Teachers disclosed that they learned it from personal experience (55.2%) and schools (29.2%).Stressful events were present in 47.3%. Physical punishment was significantly more in this category (Chi square 3.84,p 0.05). Almost 77% of teachers had received punishment during childhood. The modal age for getting last punishment was 14 years. Significantly greater number of teachers getting punishment during childhood opinioned in favor of punishing children(Chi square 5.769,p 0.016) and were also involved in this activity(Chi square 6.534,p o.o11). Conclusions: Physical punishment of school children by teachers is common. Stress in the family and punishment during childhood were significant risk factors.